Evaluasi Pengelolaan Parkir Oleh Dinas Perhubungan Kota Pekanbaru - Hendry Andry; Zulkifli Zulkifli (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
In general, the provision of parking lots by the Government is used for the whole community. In this case, the community is obliged to pay a parking fee when using the parking lot. Retribution is required to make payments to parking attendants who have been determined by the Government, especially under the guidance of the UPT Parking Department of Transportation, Pekanbaru City. In Regional Regulation Number 14 of 2016 concerning Parking Fees on Public Roads, the parking fee for 2-wheeled road users is IDR 1,000, and for 4-wheeled vehicles is IDR 2,000. but starting in early September 2022, Pekanbaru Mayor Regulation (Perwako) No. 41 of 2022 concerning Amendments to Pekanbaru Mayor Regulation No. 148 of 2020 concerning Parking Service Rates where the parking fee for two-wheeled vehicles increases to Rp. 2.000 and for cars or four-wheelers to Rp. 3.000 for one parking. The difference in parking rates between the Perda and the Perwako has resulted in practice, there are still many parking attendants who ask for retribution to pay not in accordance with predetermined rules. In addition, there are still many parking attendants who do not use parking attributes, do not provide parking tickets, and so on. This study aims to identify and describe the evaluation of parking management by the Pekanbaru City Transportation Agency using a qualitative descriptive approach with interactive model analysis techniques. The results of this study indicate that parking management has not been carried out effectively because there is no clarity regarding existing regulations so the implementation has not been carried out effectively.